Penerapan Sistem Informasi Visualisasi Data Industri Kecil menengah Dengan Menggunakan Metode Dashboard : Studi kasus Dinas Koperasi UKM dan Perindustrian Kabupaten Ogan Komering ilir - Fitri Purwaningtias; Muhamad Diki (BETRIK, 2023)
This research aims to implement a data visualization information system forsmall and medium industries (IKM) using the dashboard method. The case study wascarried out at the Ogan Komering Ilir Regency Cooperative, SME and Industry Service,with the aim of assisting decision making in the small and medium industry sector.Thedashboard method is used to present small and medium industry data visually andinteractively, making it easier for users to understand the data and make the rightdecisions. This research uses a qualitative approach with data collection techniquesthrough observation, interviews and documentation. The results of the research show thatthe application of a data visualization information system for small and medium industriesusing the dashboard method can help decision making at the Ogan Komering Ilir RegencyCooperatives, SMEs and Industry Department more quickly and accurately. Apart fromthat, this system can also provide more complete and integrated information, so that it can increase the efficiency and effectiveness of the performance of the Ogan Komering IlirRegency Cooperatives, SMEs and Industry Service.